Dekolonisasi Ekonomi dan Konservasi Hutan Berbasis Adat dalam Kosmologi Ekologis Masyarakat Tepera di Distrik Ravenirara Kabupaten Jayapura - Mangaluk, Efraim; Lada, Yulius Gae; Mandibondibo, Paulus; Apituley, Frank Leonardo; Wanaputra, Amadion Andika; Bura, Silvans Tande (Jurnal Noken: Ilmu-Ilmu Sosial, 2026)
The ecological crisis of the Anthropocene demands a re-evaluation of the technocratic conservation paradigm, which tends to subordinate the ontologies of Indigenous peoples. This study aims to reconstruct the ecological cosmology of the Tepera indigenous community in Yongsu Desoyo Village, Ravenirara District, Jayapura Regency, and to formulate a model of economic decolonization grounded in local wisdom. Employing a critical ethnographic approach through in-depth interviews with customary leaders and participant observation, the research is framed by Habermasian Modernity theory and a Critical-Practical Policy perspective. The findings reveal three principal results. First, the philosophy of Bu Suwe Kani Suwe (The Power of Water is the Power of Land) articulates a triadic water-land-tree paradigm that constitutes the ontological foundation of pre-colonial conservation practices, while the concept of Desoyo as "I am the Village Sprout" affirms that customary sovereignty is rooted in the ancestral ethnoecological verification protocols. Second, the "Sago Tree" metaphor functions as a socio-political mechanism of resilience that positions customary leadership as a source of equitable livelihood distribution. Third, the 2019 flash flood exemplifies the colonization of the lifeworld by system logic, generating a twofold vulnerability of ecological degradation and economic precarity. This study proposes a "government-as-distributor" model to sever dependency on extractive economies, while advocating the integration of customary law into public policy to facilitate Yongsu Desoyo's transition toward Customary Village (Kampung Adat) status.